Parish charity in the 18th – early 20th centuries (based on the materials of the Olonets diocese) - Pulkin Maxim Viktorovich (Studia Humanitatis, 2020)
The article discusses the problems of parish charity formation and development in the territory of the Olonets diocese. The main areas of charity were the parish churches’ construction and providing them with necessary worship property, the acquisition of vestments for the clergy. Later the support of church parish schools and assistance to the development of church singing were added to the areas of charity. The most prominent role in the development of church philanthropy was played by local merchants, who later became churchwardens. The second most important role belonged to the parishioners themselves, who actively contributed to the well-being of the local parish.